Expression of the three nitric oxide synthase isoforms and nitric oxide level in the rat heart during cold storage and blood reperfusion - Desrois, M; Caus, T; Dalmasso, C; Lan, C; Cozzone, P J; Bernard, M (Cellular and Molecular Biology, 2009)
Maintenance of nitric oxide (NO) homeostasis is an important concept for myocardial protection. Here, we have investigated the NO pathway by analysing total nitrate concentration (NOx) and NO synthase (NOS) isoforms expression as well as the myocardial integrity by lactate dehydrogenase and creatine kinase contents in the rat heart graft arrested by CRMBM solution, submitted to 3 hr cold ischemia in the same solution and 24 hr blood reperfusion following heterotopic abdominal heart transplantation. NOx level was similar to baseline value after ischemia and significantly increased after 24 hr reperfusion. NOS isoforms expression was highly modulated after cold ischemia followed by blood reperfusion. Endothelial NOS expression was decreased after ischemia but restored after 24 hr reperfusion. Neuronal NOS expression was drastically decreased after ischemia and 24 hr reperfusion. Inducible NOS protein was present only after 24 hr reperfusion. Cold ischemia induced a severe loss of creatine kinase without any modification after blood reperfusion. In conclusion, we show here that CRMBM solution did not increase NO production during ischemia but induced an enhanced synthesis of NO during reperfusion which may be related to restoration of endothelial NOS expression and/or induction of inducible NOS expression.